PENGEMBANGAN E-MODUL MENGGUNAKAN MICROSOFT SWAY UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIDIKAN PANCASILA SISWA KELAS V SDN 1 SENDANGMULYO - Sa'diyatul Jazilah; Wendri Wiratsiwi (Prodi PGSD Universitas PGRI Ronggolawe, 2024)
Technology-based teaching materials can attract students' interest and attention in the learning process. This research was conducted with the aim of developing an e-module product using microsoft sway to improve student learning outcomes. This research method is Research and Development (R&D) using the ADDIE model, namely Analysis, Design, Development, Implementation and Evaluation. The research subjects were teachers and 5th grade students of SDN 1 Sendangmulyo. Data collection techniques through observation, interviews, expert validation, questionnaires, and tests. The results of media expert validation are 96%, while the results of material expert validation are 96%. When referring to the validation criteria table, this e-module is declared valid. The results of the teacher response questionnaire are 100% while the student questionnaire is 96.6%, so based on the practicality analysis table, this e-module is declared very practical. The results of the trial conducted on grade 5 students of SDN 1 Sendangmulyo were very effective, because the percentage of students who achieved the criteria for achieving learning objectives (KKTP) was 93%. When referring to the effectiveness level criteria table, this e-module is effective.